The Quality of Service of Hospital Officers on Inpatient Patient Satisfaction at UPT. RSKD. Dadi Makassar City - Imran, Ali; Nursinah, Nursinah; B, Muslimin; Yuniarsih, Sri (Media Kesehatan Politeknik Kesehatan Makassar, 2024)
Patient satisfaction is considered fulfilled if the services provided are in accordance with their expectations. On the other hand, if the hospital provides services that do not meet the patient's expectations, then the patient will definitely feel dissatisfied. The aim of this research is to determine the quality of hospital staff service on the satisfaction of inpatients at UPT. RSKD. Dadi Makassar City. This research uses a type of quantitative research that uses a cross-sectional study design approach. This cross sectional study design is to see the relationship between the independent variable and the dependent variable. By using the chi-square statistical test, the level of significance (ɑ) = 0.05. The total population of inpatients was 470 people, and samples were taken of 82 patients at UPT. RSKD. Dadi Makassar City. The results of the research show that there is a relationship between reliability, assurance, tangible, empathy, responsiveness, responsiveness to the quality of service of hospital staff on the satisfaction of inpatients at UPT. RSKD. Dadi Makassar City, with a more significant guarantee variable with a p-value of 0.00. The research conclusion is that the quality of service at UPT. RSKD. Dadi Makassar City is proven to provide services to patients quickly and responsively, so that patients are satisfied with the services provided. Keywords: satisfaction, service quality, inpatients.